2015
DOI: 10.3382/ps/pev017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the in ovo injection of 25-hydroxycholecalciferol on the yolk and serum characteristics of male and female broiler embryos ,

Abstract: Serum concentrations of 25-hydroxycholecalciferol [25(OH)D3] in broiler embryos at 19 d of incubation:doi:have been shown to increase 3 times by the in ovo injection of 0.60 μg 25(OH)D3 on 18 doi. In this trial, effects of the injection of 25(OH)D3 at 18 doi on the yolks and sera of male and female Ross×Ross 708 broiler embryos were assessed. On 18 doi, embryonated eggs that were set in a single stage incubator were assigned to 6 replicate trays within each of 2 injection treatment groups. Treatments included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The lack of treatment effects on hatchability and mortality indicates that in ovo feeding with 25(OH)D3 at the eighth day of incubation did not result in compromised embryo development. Similar to the present study, Bello et al (2015) found no difference in EML with in ovo feeding with 0.6 µg of 25(OH) D3 at 18 days of incubation. However, Sgavioli et al (2015) reported a decrease in egg hatchability after injecting increasing levels of vitamin C before incubation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of treatment effects on hatchability and mortality indicates that in ovo feeding with 25(OH)D3 at the eighth day of incubation did not result in compromised embryo development. Similar to the present study, Bello et al (2015) found no difference in EML with in ovo feeding with 0.6 µg of 25(OH) D3 at 18 days of incubation. However, Sgavioli et al (2015) reported a decrease in egg hatchability after injecting increasing levels of vitamin C before incubation.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that in ovo inoculation of 1.25(OH)2D3, 25(OH)D3, and 24.25(OH)2D3 during incubation improves hatching, bone development, and yolk calcium concentration and interferes with receptor mRNA expression by IGF-1 (Yair et al, 2013;Bello et al, 2014a,b,c;Bello et al, 2015;Yair et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of the in ovo injection of 25OHD 3 alone at various dosage levels on the hatchability, hatching chick quality, and the posthatch production and performance of broilers have been investigated ( Gonzales et al., 2013 , Bello et al., 2013 , Bello et al., 2014a , Bello et al., 2014b , Bello et al., 2014c , Bello et al., 2015 , Mansour et al., 2017 ). However, those effects on the broiler embryo have not been investigated when D 3 is administrated at 18 doi by amniotic in ovo injection alone or in combination with 25OHD 3 .…”
Section: Results and Disscussionmentioning
confidence: 99%
“…The in ovo injection of 0.60 μg of 25OHD 3 has likewise been shown to influence the hatchability and yolk characteristics of broilers ( Bello et al., 2013 , Bello et al., 2015 ). Embryos that received an in ovo injection of 0.60 μg of 25OHD 3 exhibited higher hatchability and serum 25OHD 3 levels than embryos from a diluent-injected control group ( Bello et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%